2017
DOI: 10.5534/wjmh.2017.35.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Deficiency and Nocturia: A Review

Abstract: Nocturia causes lack of sleep and excessive daytime somnolence, reducing overall well-being, vitality, productivity, and mental health. Nocturia is significantly associated with testosterone deficiency, lower urinary tract symptoms (LUTS), and sleep disorders. The development of LUTS is commonly associated with testosterone deficiency in elderly men, and recent studies have suggested that testosterone has an ameliorative effect on nocturia. In hypogonadal men with nocturia, a negative feedback cycle can arise,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Sexual dysfunction is more common among older men, and insomnia has been found to be an independent risk factor related to sexual dysfunction, along with cardiovascular disease, diabetes, and depression [46]. The most likely explanation for the mechanism underlying the association between insomnia and sexual dysfunction is a decrease in the level of testosterone.…”
Section: Main Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual dysfunction is more common among older men, and insomnia has been found to be an independent risk factor related to sexual dysfunction, along with cardiovascular disease, diabetes, and depression [46]. The most likely explanation for the mechanism underlying the association between insomnia and sexual dysfunction is a decrease in the level of testosterone.…”
Section: Main Bodymentioning
confidence: 99%
“…A study of type 2 diabetes patients also found nocturia was associated with ED, and patients with lower levels of testosterone had a higher prevalence of nocturia [131]. It is currently considered that nocturia and testosterone have a negative feedback relationship, in which nocturia produces a decrease of testosterone, and a testosterone decline contributes to the development of nocturia in hypogonadal men with nocturia [46]. Hence, nocturia treatment could increase testosterone levels [132], and testosterone replacement therapy could decrease the frequency of nocturia in reverse [133].…”
Section: Main Bodymentioning
confidence: 99%
“…Next, to the possible effects of transurethral resection of the prostate (TURP) and open surgery on plasma levels of testosterone, it has been shown that surgical stress and general anesthesia produce a decrease of serum testosterone 25,26 which may disturb urine concentrating ability (by lowering vasopressin levels), sleeps quality and metabolic parameters. 27 The temporary nature of all the mechanisms aforementioned can hardly explain persisting de novo nocturnal LUTS.…”
Section: Nocturiamentioning
confidence: 99%
“…Depletion of testosterone is associated with loss of muscle mass and bone strength, reduced bone mineral density, sexual dysfunction, deterioration of insulin sensitivity, elevated visceral fat and metabolic syndrome, all of which are on the causal pathway of nocturia. 18 Loss of testosterone also alters circadian rhythms, thermoregulation during the night and sleep quality. Testosterone production may be impaired by interrupted deep sleep or sleep apnoea.…”
Section: Question 5: How Much Urine Do You Make Over Night?mentioning
confidence: 99%